AKIBAT HUKUM HAK ASUH ANAK TERHADAP PERCERAIAN KARNA MURTAD DI PENGADILAN AGAMA PEKANBARU - Azhimy, Rais; Ismi, Hayatul; Diana, Ledy (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Nowadays, child custody is often a problem before or after divorce. In fact, it is not uncommon for ex-husbands and ex-wives to struggle to get custody of their children, because children are the hope of parents who are difficult to separate. The child is the party who is disadvantaged by the divorce of both parents. The child loses the love that is needed completely from both parents, there is no child who only wants to get love from his father or mother, besides that income and education are also not free from the role of parents. The best condition for children is if the child is in the care of both parents, because good care and care as well as optimal attention from both of them will build physically and psychologically and prepare the child carefully to live life.The problems that the authors make the basis of in this study are what are the consequences of child custody law due to divorce due to apostasy and what are the children's rights that must be fulfilled when a divorce occurs due to apostasy parents.This type of research used by the author is sociological legal research, which is also called doctrinal legal research. This normative research is a study that discusses the principles of law, legal systematics, the level of legal synchronization, legal history and legal comparisons. From this sociological legal research, the author is interested in conducting research using legal systematic criteria.The results of this study are the first in the PA decision no. 1366 / Pdt.G / 2018 / Pa.Pbr the judge decided the case based on Article 116 letter (h), namely divorce can occur because one of the parties has changed religions or an apostate,in this case there is no discussion of child custody, child custody according to the author given to the mother because at the time of the divorce process the child wasunderage, in the compilation of Islamic law it is known as the right of haddnah, namely custody of minors given to the mother, both as stated in article 41 of Law No.1 of 1974 concerning marriage are known There are several consequences of breaking a marriage bond due to divorce, including: A divorced father and mother are still obliged to care for and educate their children, based purely on the needs of the child. If there is a dispute about child mastery. then the court has the right to give its decision. The father is the party responsible for all the costs of maintaining and educating the child. If it turns out that the father is not able to fulfill this obligation, the court will determine that the mother is also responsible for the costs. The court can require the ex-husband to provide living expenses and or determine the obligations of the ex-wife.Keywords: Divorce, Marriage, Child Custody